The role of molybdenum in suppressing cold dwell fatigue in titanium alloys. (31st July 2017) - Ready, Adam J.; Haynes, Peter D.; Grabowski, Blazej; Rugg, David; Sutton, Adrian P.
Abstract : We test a hypothesis to explain why Ti-6242 is susceptible to cold dwell fatigue (CDF), whereas Ti-6246 is not. The hypothesis is that, in Ti-6246, substitutional Mo-atoms in α-Ti grains trap vacancies, thereby limiting creep relaxation. In Ti-6242, this creep relaxation enhances the loading of grains unfavourably oriented for slip and they subsequently fracture. Using density functional theory to calculate formation and binding energies between Mo-atoms and vacancies, we find no support for the hypothesis. In the light of this result, and experimental observations of the microstructures in these alloys, we agree with the recent suggestion (Qiu et al. 2014 Metall. Mater. Trans. A 45, 6075–6087. (doi:10.1007/s11661-014-2541-5 )) that Ti-6246 has a much smaller susceptibility to CDF because it has a smaller grain size and a more homogeneous distribution of grain orientations. We propose that the reduction of the susceptibility to CDF of Ti-6242 at temperatures above about 200° C is due to the activation of 〈c +a 〉 slip in 'hard' grains, which reduces the loading of grain boundaries.